On the Melting and Disordering of Thin Epitaxial Films - A. Patrykiejew; S. Sokolowski (Adsorption Science & Technology)
The disordering of thin films formed on the (100) plane of the face centred cubic (fcc) crystal was studied by the Monte Carlo simulation method. It was shown that the adsorbed films, which order into the (1 × 1) structure in each layer at low temperatures, disorder in a layer-by-layer mode, at least for films with thicknesses of up to 12 layers. It was also demonstrated that, with increasing film thickness, the temperature at which the film disorders depended on the strain resulting from the mismatch between the sizes of the adsorbate atoms and the surface lattice.